Self-organization of rectangular bipyramidal helical columns by supramolecular orientational memory epitaxially nucleated from a Frank-Kasper σ phase. (March 2022) - Percec, Virgil; Huang, Ning; Xiao, Qi; Partridge, Benjamin E.; Sahoo, Dipankar; Imam, Mohammad R.; Peterca, Mihai; Graf, Robert; Spiess, Hans-Wolfgang; Zeng, Xiangbing; Ungar, Goran
Highlights: SOM observed first time from a non-cubic giant tetragonal lattice known as Frank-Kasper σ phase. Rectangular bipyramidal arrangement of helical hexagonal columns was induced by SOM. SOM induced by close contact spheres of the σ phase by epitaxial nucleation. Abstract: Programming living and soft complex matter via primary structure and self-organization represents the key methodology employed to design functions in biological and synthetic nanoscience. Memory effects have been used to create commercial technologies including liquid crystal displays and biomedical applications based on shape memory polymers. Supramolecular orientational memory (SOM), induced by an epitaxial nucleation mediated by the close contact spheres of cubic phases, emerged as a pathway to engineer complex nanoscale soft matter of helical columnar hexagonal arrays. SOM preserves the crystallographic directions of close contact supramolecular spheres from the 3D phase upon cooling to the columnar hexagonal periodic array. Despite the diversity of 3D periodic and quasiperiodic nanoarrays of supramolecular dendrimers, including Frank-Kasper and quasicrystal, all examples of SOM to date were mediated by I m 3 ¯ m (body-centered cubic, BCC) and P m 3 ¯ n (Frank-Kasper A15) cubic phases. Expanding the scope of SOM to non-cubic arrays is expected to generate additional morphologies that were not yet available by any other methods. Here we demonstrate the SOM of a dendronized triphenylene that self-organizes into helical columnar hexagonal and tetragonal P4 2 /mnm (Frank-Kasper σ) phases. Structural analysis of oriented fibers by X-ray diffraction reveals that helical columnar hexagonal domains self-organize an unusual rectangular bipyramidal morphology upon cooling from the σ phase. The discovery of SOM in a non-cubic Frank-Kasper phase indicates that this methodology may be expanded to other periodic and quasiperiodic nanoarrays organized from self-assembling dendrimers and, most probably, to other soft and living complex matter. Graphical abstract: Image, graphical abstract